Agreement of simplified Fencl-Stewart with Figge-Stewart method in diagnosing metabolic acidosis in critically ill children - Rotua Sinaga; Abdurachman Sukadi; Dadang Hudaya Somasetia (Indonesian Pediatric Society Publishing House, 2007)
Background The traditional Henderson-Hasselbalch approach has proven to be imprecise in critically ill patients. Stewart's approach can detect metabolic acidosis missed by traditional approach, including acidosis caused by increased unmeasured agreement (UA). The complexity of Stewart's method leads to development of simpler modifications, simplified Fencl-Stewart and Figge- Stewart method. Agreement between both modifications is unknown. Objective This study aimed to measure the agreement of simplified Fencl-Stewart with Figge-Stewart method in diagnosing metabolic acidosis in critically ill children. Methods The was performed in Hasan Sadikin General Hospital, Bandung from July to August 2006, involving <14 year-old critically ill children. Blood samples for gas analysis, sodium, potassium, chloride and albumin measurement were taken simultaneously. Test result was analyzed with simplified Fencl-Stewart and Figge-Stewart method and recorded with Excell spreadsheet. PASS was used for interim analysis and DAG_Stat for raw agreement indices and Kappa calculations. Results Forty-five (31 males, 14 females) children were enrolled. Acid base disturbances based on Stewart's method were identified in 10 subjects with normal base excess and nine with normal bicarbonate. Significant increase of UA was detected in 11 of 45 subjects with simplified Fencl-Stewart method, compared to that of 12 subjects with Figge-Stewart method. Raw agreement indices showed 95.65% and 98.51% agreement for positive and negative result, Kappa was 0.94 (P=0.0000). Conclusions Excellent agreement is shown between simplified Fencl-Stewart and Figge-Stewart method in diagnosing metabolic acidosis in critically ill children. Increased UA can be assessed with both methods.